2022
DOI: 10.1097/meg.0000000000002414
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of pharmacologic treatment for treating gastrointestinal angiodysplasias-related bleeding: a systematic review and meta-analysis

Abstract: Introduction We evaluated the efficacy of pharmacologic treatments for patients with overt or occult bleeding due to gastrointestinal angiodysplasias (GIADs). Methods A systematic computer-aided literature search across Medline, Cochrane, Scopus and Embase databases was performed. Studies evaluating pharmacologic treatments for patients presenting with GIADs-related overt or occult bleeding were included. Post-treatment rebleeding was the primary outcome. Need for red blood cells (RBC) transfusion, post-trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Our findings are consistent with previous meta-analyses that included both RCTs and observational studies. 5 Pharmacologic treatment of GI angiodysplasias showed a significant reduction in the incidence of rebleeding [odds ratio (OR) = 0.08, 95% CI: 0.04–0.18, I 2 = 50%], and improvement in hemoglobin levels (MD = 3.21 g/dl, 95% CI: 2.42–3.99). Moreover, no participants discontinued treatment due to adverse effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are consistent with previous meta-analyses that included both RCTs and observational studies. 5 Pharmacologic treatment of GI angiodysplasias showed a significant reduction in the incidence of rebleeding [odds ratio (OR) = 0.08, 95% CI: 0.04–0.18, I 2 = 50%], and improvement in hemoglobin levels (MD = 3.21 g/dl, 95% CI: 2.42–3.99). Moreover, no participants discontinued treatment due to adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“… 3 And the small bowel is the most common site of GI angiodysplasias, accounting for approximately 80% of cases, followed by colon (44%) and the stomach (32%). 4 , 5 GI angiodysplasias contribute to about 60% of small bowel bleeding cases. 6 Bleeding tends to be recurrent, can pose a life-threatening risk due to the need for large transfusions and potential emergent hemostatic interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Related to this, a recent systematic review and meta-analysis evaluated the efficacy of treatment GIADs related bleeding with somatostatin analogues, hormonal therapies, thalidomide and bevacizumab. Despite all showing comparable efficacy, thalidomide was proven to have the highest risk of side effects as well as a higher rebleeding rate following treatment in comparison to bevacizumab [15].…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of 25 studies revealed that somatostatin analogs, hormonal therapy, thalidomide and angiogenesis inhibitors all reduced bleeding episodes (OR 0.08, 95%CI 0.04-0.18), transfusion requirements (OR 0.03, 95%CI 0.03-0.07), and hemoglobin drops, and no pharmacological treatment was superior to the others (P=0.83) [ 77 ]. However, the choice of pharmacological agent should be guided by a knowledge of patient characteristics and side-effect profile.…”
Section: Noninvasive Managementmentioning
confidence: 99%